Changes in foliage and canopy of oil-impacted mangrove trees in selected areas of TINMAR, Nueva Valencia, Guimaras - Obligacion, Henlen Mae Q.
On August 11, 2006, the tanker MT Solar I sank approximately 10 nautical miles south of Guimaras Island in Western Visayas. The Solar I oil spill incident was the largest oil spill recorded to date in the Philippines, which involved the release of more thantwo (2) million liters of oil into the sea. Many sensitive habitats including the mangrove forests within the Taklong Island National Marine Reserve (TINMAR), Nueva Valencia, Guimaras were affected. The present paper reports on the monitoring of the health conditions of three species of mangroves found in TINMAR. These species included Rhizophora stylosa, Rhizophora mucronata, and Avicennia marina. This studyaimed to determine the effects of oil on growth and development in foliage and canopy of selected mangrove tree species both in Taklong Island and Sitio Bagatnan from August 2007 and February 2008. Measurements were taken on the three species of mangroves in order to determine any sublethal impact and growth abnormalities. Measurements recorded include: leaf production (total number of leaves per branch), leaf size, and any unusual growth patterns that may have developed as a result of oil contamination. Results showed a significant reduction in leaf size (p<0.05) of Rhizophora stylosa, Rhizophora mucronata, and Avicennia marina, on trees found in oiled sites against those unoiled control site. Leaf production (number of leaves) of Rhizophora mucronata and Avicennia marina reduced in the unoiled site. However, Rhizophora stylosa exhibited a greater leaf production on the unoiled site. This results of this study that oil affects each of the mangrove species differently. Rhizophora trees are less tolerant to oiling that that shown in Avicennia marina trees in the area of oil contamination. In conclusion, these results suggest that crude oil have negative consequences on mangroves. Changes in leaf development evident in leaf size and leaf production reductions are useful indicators of sub-lethal stress experienced by mangroves exposed to oil for long-term monitoring purposes.